Answer:
Step-by-step explanation:
It is given that In parallelogram DEFG,
DH = x + 1
HF = 3y
GH = 3x - 4
and HE = 5y + 1
Since, DH,HF, GH and HE represents the diagonals of the parallelogram and also we know that the diagonals of parallelogram bisect each other, therefore
x+1=3y (1)
3x-4=5y+1 (2)
Multiply equation (1) with 3 and then subtract equation (2) from it, we get
3x+3-3x+4=9y-5y-1
7=4y-1
y=2
Substitute the value of y=2 in equation (1), we get
x+1=3(2)
x=5
Thus,the value of x and y are 5 and 2 respectively.